REVIEW OF THE BOOK "RESEARCH INTO THE PSYCHOLOGICAL PECULIARITIES OF CHILDREN AND ADOLESCENTS" BY TSVETELINA HADZHIEVA, PH.D - Mavrodiev, Stoil Lyubenov (Psychological thought, 2025)
The review presents the monograph of Chief Assistant Professor Tsvetelina Hadzhieva, Ph.D. "Study of the psychological features of the child and adolescent", in which the author has made a thorough and informative theoretical review of the issues under consideration, supported by scientific research and modern concepts on child and adolescent development. Each of the issues discussed carries its own persuasiveness and relevance, supported by scientific facts and a clearly expressed position on the part of the head Chief assistant Hadzhieva.